ROS Induced by Streptococcus agalactiae Activate Inflammatory Responses via the TNF-α/NF-κB Signaling Pathway in Golden Pompano Trachinotus ovatus (Linnaeus, 1758) - Jie Gao; Mingjian Liu; Huayang Guo; Kecheng Zhu; Bo Liu; Baosuo Liu; Nan Zhang; Dianchang Zhang (MDPI AG, 2022)
Streptococcus agalactiae is common pathogenic bacteria in aquaculture and can cause mass mortality after fish infection. This study aimed to investigate the effects of S. agalactiae infection on the immune and antioxidant regulatory mechanisms of golden pompano (Trachinotus ovatus). Serum and liver samples were obtained at 0, 6, 12, 24, 48, 96, and 120 h after golden pompano infection with S. agalactiae for enzyme activity and gene expression analyses. After infection with S. agalactiae, the content of reactive oxygen species (ROS) in serum was significantly increased (p < 0.05). Serum levels of glucose (GLU), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and malondialdehyde (MDA) increased and then decreased (p < 0.05), reaching a maximum at 6 h. Serum antioxidant enzyme (LZM) activity increased significantly (p < 0.05) and reached a maximum at 120 h. In addition, the mRNA expression levels of antioxidant genes (SOD, CAT, and GPx) in the liver increased and then decreased, reaching the maximum at 24 h, 48 h, and 24 h, respectively. During the experimental period, the mRNA expression levels of NF-κB-related genes of the inflammatory signaling pathway inhibitory κB (IκB) showed an overall decreasing trend (p < 0.05) and the lowest expression at 120 h, whereas the mRNA expression levels of tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), IκB kinase (IKK), and nuclear factor NF-κB increased significantly (p < 0.05) and the highest expression was at 120 h. In conclusion, these results showed that S. agalactiae could activate internal regulatory signaling in the liver of golden pompano to induce defense and immune responses. This study is expected to lay a foundation to develop the healthy aquaculture of golden pompano and promote a more comprehensive understanding of its disease resistance mechanisms.